Estudio de factibilidad para la creación de un centro de acopio para la distribución y comercialización de gas doméstico (GLP) cantón Pangua, año 2014. - Ortíz Guevara, Luis Patricio (2016)
The feasibility study for setting up a collection center for domestic distribution and marketing of gas in the canton Pangua, is very well accepted in a lot of families. For observations of feasibility study took into account the market in which the supply, demand and price market was analyzed; a survey of 346 families in the canton and distributors covering the route of Pangua and surroundings was performed. Technical analysis study was conducted resource requirements for the production process starting from the structural and technological. With the economic analysis an initial investment of US $ 187341.67 which will be represented by the contribution of 50% of shareholders and 50% by a bank loan taken for the parties to the implementation of the project with a rate of return is estimated 47% and a cost-benefit ratio of production of US $ 1.21. By presenting the results of research regarding the feasibility of the project the hypothesis at baseline is checked, as their viability is determined for implementation.